'Neither Completely Guilty nor Completely Innocent': Representing Injustice in Jean Racine's Phèdre. Issue 2 (2nd July 2020) - Bizer, Marc
Abstract : The eponymous protagonist of Phèdre emerges as a true tragic heroine by exercising her own free will to commit wrong instead of being a mere victim of fate. Criticism focusing on injustice has tended to shine light on Thésée, denying Phèdre royal sovereignty just as French Salic law did to queens. By shifting the spotlight from Thésée to Phèdre, and from the idea of judgment as a means of redressing injustice to injustice resulting from the challenges of governance and self–governance in royal leaders, we will see that Phèdre's gender has tended to obscure the important connection between injustice and the exercise of monarchical power. The gender of the eponymous heroine of the play operates as a cover: by associating wrongdoing with a female monarch, a literal impossibility in France, Racine is able to delve into particularly controversial aspects of unjust governance as experienced in his day and age.